The Implementation of Remuneration Based Performance in Sharia State University in Indonesia - Indah Puji Astuti (Relevance: Journal of Management and Business, 2018)
The purpose of this study is to determine: the implementation of remuneration based performance in sharia state university in Indonesia (IAIN-Institut Agama Islam Negeri). This study aims to determine the influence of remuneration, job satisfaction, achievement motivation, and organizational culture on employee performance. Research method used in this study using a survey within the university staff. The multiple regression results indicate that remuneration, job satisfaction, achievement motivation, and organizational culture has a significant positive contribution to the performance of employees.